Temporal Patterns and Adoption of Germline and Somatic BRCA Testing in Ovarian Cancer. Issue 5 (5th November 2022) - Huepenbecker, Sarah P.; Wright, Jason D.; Downer, Mary K.; Incerti, Devin; Luhn, Patricia; Dolado, Ignacio; Bastiere-Truchot, Lydie; Lin, Yvonne G.; Chan, John K.; Meyer, Larissa A.
Abstract : In a large cohort of patients with ovarian cancer, testing for germline and somatic BRCA mutations has increased over time, but significant practice disparities exist. Abstract : OBJECTIVE: To describe the testing rate, patient characteristics, temporal trends, timing, and results of germline and somatic BRCA testing in patients with ovarian cancer using real-world data. METHODS: We included a cross-sectional subset of adult patients diagnosed with ovarian cancer between January 1, 2011, and November 30, 2018, who received frontline treatment and were followed for at least 1 year in a real-world database. The primary outcome was receipt of BRCA testing, classified by biosample source as germline (blood or saliva) or somatic (tissue). Lines of therapy (frontline, second line, third line) were derived based on dates of surgery and chemotherapy. Descriptive statistics were analyzed. RESULTS: Among 2, 557 patients, 72.2% (n=1, 846) had at least one documented BRCA test. Among tested patients, 62.5% (n=1, 154) had only germline testing, 10.6% (n=197) had only somatic testing, and 19.9% (n=368) had both. Most patients had testing before (9.7%, n=276) or during (48.6%, n=1, 521) frontline therapy, with 17.6% (n=273) tested during second-line and 12.7% (n=129) tested during third-line therapy. Patients who received BRCA testing, compared with patients without testing, were younger (mean age 63 years vs 66 years, P <.001) and were more likely to be treated at an academic practice (10.4% vs 7.0%, P =.01), with differences by Eastern Cooperative Oncology Group performance score ( P <.001), stage of disease ( P <.001), histology ( P <.001), geography ( P <.001), and type of frontline therapy ( P <.001), but no differences based on race or ethnicity. The proportion of patients who received BRCA testing within 1 year of diagnosis increased from 24.6% of patients in 2011 to 75.6% of patients in 2018. CONCLUSION: In a large cohort of patients with ovarian cancer, significant practice disparities existed in testing for actionable BRCA mutations. Despite increased testing over time, many patients did not receive testing, suggesting missed opportunities to identify patients appropriate for targeted therapy and genetic counseling.